Multi-solid-waste ultra-high-performance concrete as well as preparation method and application thereof
By using recycled fine aggregates, iron tailings sand, recycled fine powder, steel slag powder and steel fiber in ultra-high performance concrete, the existing ultra-high performance concrete is solved, and the multi-solid waste ultra-high performance concrete with high compressive strength and good economic and environmental benefits are achieved.
Patent Information
- Application Number
- CN202411656953.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-04-04
AI Technical Summary
The existing ultra-high performance concrete has shortcomings in cost and environmental friendliness, which hinders its further promotion and application.
By using recycled fine aggregates and iron tailings sand to replace quartz sand, recycled fine powder and steel slag powder to replace gelling materials, and adding appropriate amounts of steel fibers, multi-solid waste ultra-high performance concrete with high compressive strength is prepared.
A compressive strength of 28 days was achieved ≥120 MPa, which meets the requirements of ultra-high performance concrete, while reducing costs, and has good economic and environmental benefits.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and in particular to a multi-solid waste ultra-high performance concrete and a preparation method thereof. Background Art
[0002] Ultra-High Performance Concrete (UHPC) is a new type of cement-based composite material with ultra-high strength, excellent toughness and durability. It shows great potential and value in civil engineering. Different from ordinary concrete, it requires higher quality raw materials, lower water-cement ratio, higher proportion of cementitious materials, less use of coarse aggregate, and has disadvantages such as high cost, which hinders its further promotion and application.
[0003] With the development of industrialization and urbanization in my country, the amount of bulk solid waste generated has increased year by year. A large amount of solid waste is disposed of by landfill and storage, with a low comprehensive utilization rate, which not only pollutes the environment, but also occupies a large amount of land, which is not conducive to the green development of the social economy. If bulk solid wastes such as construction waste, steel slag, and tailings can be used as raw materials to replace the high-quality and high-cost raw materials for preparing multi-solid waste ultra-high performance concrete, it can not only effectively reduce the manufacturing cost of ultra-high performance concrete, but also realize the high-value application of bulk solid waste, and achieve green and low-carbon.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] 1. Technical issues to be resolved The object of the present invention is to provide a multi-solid waste ultra-high performance concrete, which uses recycled fine aggregate and iron tailings sand to replace quartz sand, recycled micro powder and steel slag powder to replace cementitious materials, and is added with an appropriate amount of steel fiber. The compressive strength of the concrete at 28 days is ≥120 MPa, which meets the requirements of ultra-high performance concrete and has good economic and environmental benefits. Another object of the present invention is to provide a preparation method and application of the multi-solid waste ultra-high performance concrete.
[0006] (II) Technical solution Specifically, the present invention provides the following technical solutions: A multi-solid waste ultra-high performance concrete, comprising cement, silica fume, fly ash, steel fiber, quartz sand, a water reducer, water, at least one of recycled micro powder and steel slag powder, and at least one of recycled fine aggregate and iron tailings sand, wherein, in terms of mass ratio, the sum of cement: recycled micro powder and steel slag powder is 6:1-4:3, and the sum of quartz sand: recycled fine aggregate and iron tailings sand is 7:4-3:8.
[0007] The multi-solid waste ultra-high performance concrete according to the present invention has a 28-day compressive strength of ≥120 MPa and has good economic and environmental benefits.
[0008] In some embodiments, the total amount of cement, recycled micro powder and steel slag powder is 70 parts relative to the total amount of silica fume, fly ash and steel fiber, which is 46 parts.
[0009] Even if the total amount of cement, recycled micro powder and steel slag powder is 70 parts, the compressive strength at 28 days is still ≥120 MPa, with higher economic and environmental benefits.
[0010] In some embodiments, the total amount of quartz sand, recycled fine aggregate and iron tailings sand is 110 parts relative to the total amount of silica fume, fly ash and steel fiber, which is 46 parts.
[0011] Even if the total amount of quartz sand, recycled fine aggregate and iron tailings sand is 110 parts, the compressive strength at 28 days is still ≥120 MPa, with higher economic and environmental benefits.
[0012] In some embodiments, the regenerated micropowder is mechanically activated to have a particle size of 8 to 20 μm.
[0013] After mechanical activation treatment, the recycled micropowder can effectively replace the amount of cement, so that the prepared multi-solid waste ultra-high performance concrete meets the performance requirements and has a better effect.
[0014] In some embodiments, the steel slag powder is prepared by mineralization activation treatment of steel slag powder under the conditions of a liquid-to-solid ratio of 0.2 and a carbon dioxide concentration of 20%.
[0015] After the steel slag powder is treated with mineralization and activation, the performance index reaches the steel slag powder of Class I requirement, which can effectively replace the amount of cement, so that the prepared multi-solid waste ultra-high performance concrete meets the performance requirements and has a better effect.
[0016] In some embodiments, the quartz sand has a mesh size of 4 to 70.
[0017] Using the above-mentioned quartz sand will achieve better results.
[0018] In some embodiments, the mixing mass ratio of each particle size in the quartz sand is 4~10 mesh: 10~26 mesh: 26~40 mesh: 40~70 mesh = 252:245:116:95.
[0019] When the mixing mass ratio of each particle size in quartz sand is 4-10 mesh: 10-26 mesh: 26-40 mesh: 40-70 mesh = 252:245:116:95, the compactness and mechanical properties of the multi-solid waste ultra-high performance concrete are better.
[0020] In some embodiments, the water reducing agent has a water reducing rate of >30%.
[0021] The water-cement ratio can be reduced by increasing the water reduction rate of the water-reducing agent to more than 30%.
[0022] The present invention also provides a method for preparing the above-mentioned multi-solid waste ultra-high performance concrete, which comprises the following steps: (1) adding cement, silica fume, fly ash, and at least one of recycled micro powder and steel slag powder into a mixer and stirring to obtain a powder mixture; (2) adding water and a water reducing agent to the powder mixture obtained in step (1) while stirring, stirring for 1 to 2 minutes, then adding quartz sand and at least one of recycled fine aggregate and iron tailings sand, stirring for 1 to 3 minutes, and then adding steel fiber, stirring for 3 to 8 minutes, to obtain a high-solid waste ultra-high performance concrete.
[0023] The multi-solid waste ultra-high performance concrete obtained by the preparation method of the multi-solid waste ultra-high performance concrete provided by the present invention has a 28-day compressive strength of ≥120 MPa, and has good economic and environmental benefits.
[0024] The present invention also provides the application of the above-mentioned multi-solid waste ultra-high performance concrete in building materials.
[0025] The multi-solid waste ultra-high performance concrete provided by the present invention has a 28-day compressive strength of ≥120 MPa, and has good economic and environmental benefits, and is particularly suitable for decorative concrete or bridge deck paving.
[0026] (III) Beneficial effects According to the present invention, by using recycled fine aggregate and iron tailings sand instead of quartz sand, recycled micro powder and steel slag powder instead of cementitious materials, and adding a proper amount of steel fiber, the 28-day compressive strength is ≥120 MPa, which meets the requirements of ultra-high performance concrete, saves costs, and has good economic and environmental benefits. DETAILED DESCRIPTION
[0027] Hereinafter, some materials in the present invention will be described.
[0028] Recycled micro powder refers to the recycled materials which are discarded concrete blocks, bricks, building blocks and other construction wastes which are screened, crushed step by step and ground into fine particles with a particle size less than 0.16mm. They mainly come from discarded concrete and discarded clay bricks in construction waste.
[0029] The activation treatment of the regenerated micropowder refers to stimulating the potential activity in the regenerated micropowder through certain physical or chemical methods, so that it can better participate in the hydration reaction and improve its performance in materials such as concrete. The appropriate treatment method can be selected according to the actual situation. In some embodiments, the regenerated micropowder is generated during the treatment of cement-based construction waste. In some embodiments, the regenerated micropowder is mechanically activated and the particle size reaches 8 to 20 μm.
[0030] Steel slag powder is a powder material obtained by extracting iron from the slag produced by steelmaking and crushing it into powder. Steel slag powder contains a high content of silicates and alkaline oxides.
[0031] The activation treatment of steel slag powder refers to improving the reactivity of steel slag powder through certain physical or chemical methods, so that it can better participate in the hydration reaction and improve its performance and application value in building materials. The appropriate treatment method can be selected according to the actual situation. In some embodiments, the steel slag powder is obtained by activating the steel slag powder under the conditions of a liquid-to-solid ratio of 0.2 and a carbon dioxide concentration of 20%.
[0032] For the multi-solid waste ultra-high performance concrete of the present invention, the sum of cement: recycled micro powder and steel slag powder is 6:1 to 4:3 in terms of mass ratio. In some embodiments, the sum of cement: recycled micro powder and steel slag powder can be 5:2.
[0033] Recycled fine aggregate refers to particles with a particle size of less than 4.75 mm that are processed from production activities such as demolition, construction, and decoration, as well as concrete, mortar, stone, bricks, and tiles in stock construction waste. In some embodiments, the recycled fine aggregate is generated during the treatment of cement-based construction waste.
[0034] Iron tailings sand refers to the waste particles with a particle size less than 4.75mm produced after the waste after ore dressing is ground and sorted.
[0035] The multi-solid waste ultra-high performance concrete in the present invention, in addition to cement, quartz sand, water reducing agent, at least one of recycled micro powder and steel slag powder, and at least one of recycled fine aggregate and iron tailings sand, also contains silica fume, fly ash, steel fiber and water.
[0036] The multi-solid waste ultra-high performance concrete of the present invention comprises the following components in parts by weight: 40-70 parts of cement, 20 parts of silica fume, 10 parts of fly ash, 0-30 parts of recycled micro powder, 0-30 parts of steel slag powder, 30-70 parts of quartz sand, 0-40 parts of recycled fine aggregate, 0-40 parts of iron tailings sand, 16 parts of steel fiber, 1.5-3 parts of polycarboxylic acid high-performance water reducer, and 15-18 parts of water.
[0037] In some embodiments, the total amount of cement, recycled micro powder and steel slag powder is 70 parts relative to the total amount of silica fume, fly ash and steel fiber, which is 46 parts.
[0038] In some embodiments, the total amount of the quartz sand, recycled fine aggregate and iron tailings sand is 110 parts relative to the total amount of silica fume, fly ash and steel fiber, which is 46 parts.
[0039] Quartz sand is a kind of quartz particles made by crushing quartz stone. The mesh number requirement of quartz sand mainly depends on its particle size distribution and specific application. The quartz sand used in the present invention is 4-70 mesh, and the mixed mass ratio of each particle size in the quartz sand is 4-10 mesh: 10-26 mesh: 26-40 mesh: 40-70 mesh = 252:245:116:95.
[0040] Water reducer is a chemical additive in concrete, mainly used to improve the plasticity and fluidity of concrete. There are mainly polycarboxylic acid series, naphthalene series, melamine series, aminosulfonate series, fatty acid series high water reducers, which can be appropriately selected according to the situation. In some embodiments, the water reducer is a polycarboxylic acid high-performance water reducer. The water reduction rate of the water reducer used in UHPC is usually above 25%. In some embodiments, the water reduction rate of the water reducer is greater than 30%. In some embodiments, the water reducer is a polycarboxylic acid high-performance water reducer.
[0041] In ultra-high performance concrete (UHPC), commonly used cement types mainly include ordinary Portland cement, high-strength, low-alkalinity cement, sulfate-resistant cement, and white cement, which can be appropriately selected based on their strength and durability. In some embodiments, the cement is ordinary Portland cement.
[0042] (Preparation method of multi-solid waste ultra-high performance concrete) The method for preparing multi-solid waste ultra-high performance concrete of the present invention comprises the following steps: (1) adding cement, silica fume, fly ash, and at least one of recycled micro powder and steel slag powder into a mixer and stirring to obtain a powder mixture; (2) adding water and a water reducing agent to the powder mixture obtained in step (1) while stirring, stirring for 1 to 2 minutes, then adding quartz sand and at least one of recycled fine aggregate and iron tailings sand, stirring for 1 to 3 minutes, and then adding steel fiber, stirring for 3 to 8 minutes, to obtain a high-solid waste ultra-high performance concrete.
[0043] In step (2), the time for stirring the mixture of water, water reducing agent and the powder obtained in step (1) is usually 1 to 2 minutes, and can be 1 minute.
[0044] The stirring time after adding quartz sand and at least one of recycled fine aggregate and iron tailings sand is usually 1 to 3 minutes, and can be 1 to 2 minutes, or 2 minutes.
[0045] The stirring time after adding the steel fiber is usually 3 to 8 minutes, and can be 3 to 5 minutes, or even 5 minutes.
[0046] Ultra-high performance concrete is widely used in building materials such as bridge engineering, building facades and decoration, urban furniture and garden landscaping, structural reinforcement and on-site emergency repairs, pipelines, underground pipe gallery projects, projects with high impact requirements, offshore oil platforms, national defense projects and protective structures, high-rise buildings and special structures.
[0047] Hereinafter, the present invention will be described using examples. However, these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0048] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.
[0049] Example 1 This embodiment provides a multi-solid waste ultra-high performance concrete, and its formula is as follows: Ordinary Portland cement 400kg / m 3 , silica fume 200kg / m 3 , fly ash 100kg / m 3 , Recycled micro powder 150kg / m 3 , steel slag powder 150kg / m 3 , quartz sand of 4~70 mesh 700kg / m 3 , recycled fine aggregate 200kg / m 3 , iron tailings 200kg / m 3 , steel fiber 160kg / m 3 , polycarboxylic acid high performance water reducing agent 18kg / m 3 , water 180kg / m 3 .
[0050] The models and processing methods of each raw material are as follows: Ordinary Portland cement: PO 42.5; Silica fume: Grade 95; Fly ash: Class I fly ash; Recycled micro powder: made from cement-based construction waste through mechanical activation; Steel slag powder: It is made by activating steel slag and granulated blast furnace slag at a liquid-to-solid ratio of 0.2 and a carbon dioxide concentration of 20%; Recycled fine aggregate: Cement-based construction waste is crushed and sieved to a particle size of ≤4.75 mm; Iron tailings sand: The waste after beneficiation is ground and sorted to a particle size of ≤4.75 mm; Steel fiber: length 10mm, diameter 0.12mm.
[0051] The preparation method of multi-solid waste ultra-high performance concrete is as follows: Put cement, silica fume, fly ash, recycled micro powder and steel slag powder into a planetary mixer dedicated to UHPC to obtain a powder mixture; While stirring, water and water reducing agent were added to the powder mixture obtained above, stirred for 1 minute, and then quartz sand, recycled fine aggregate and iron tailings sand were added, stirred for 2 minutes, and then steel fiber was added and stirred for 5 minutes to obtain a multi-solid waste ultra-high performance concrete.
[0052] Embodiment 2~7 The formulas of the multi-solid waste ultra-high performance concrete provided in Examples 2 to 7 are shown in Table 1. The multi-solid waste ultra-high performance concrete was prepared by the same preparation method as in Example 1 except that the mix ratio was changed.
[0053] Comparative Example 1 This comparative example provides a multi-solid waste ultra-high performance concrete, which is different from Example 1 in that: in the formula, no recycled micro powder, steel slag powder, recycled fine aggregate, and iron tailings sand are added. In addition, the polycarboxylic acid high-performance water reducer is 15kg / m 3 Except for changing the mix ratio, the same preparation method as in Example 1 was used to prepare the high-solid waste ultra-high performance concrete.
[0054] Comparative Example 2 This comparative example provides a multi-solid waste ultra-high performance concrete, which is different from Example 1 in that: in the formula, quartz sand and iron tailings sand are not added, and in addition, the polycarboxylic acid high-performance water reducer is 35 kg / m 3 Except for changing the mix ratio, the same preparation method as in Example 1 was used to prepare the high-solid waste ultra-high performance concrete.
[0055] Comparative Example 3 This comparative example provides a multi-solid waste ultra-high performance concrete, which is different from Example 1 in that: in the formula, no recycled fine aggregate and quartz sand are added, and in addition, the polycarboxylic acid high-performance water reducer is 25kg / m 3 Except for changing the mix ratio, the same preparation method as in Example 1 was used to prepare the high-solid waste ultra-high performance concrete.
[0056] Table 1 Formulas of various solid waste ultra-high performance concrete (Unit: kg / m 3 )
[0057] The compressive strength and flexural strength of the multi-solid waste ultra-high performance concrete obtained in the examples and comparative examples were tested according to GB 50081-2019, and the results are shown in Table 2.
[0058] Table 2 Performance of various solid waste ultra-high performance concrete
[0059] As shown in Table 2, compared with Comparative Example 1, the 28d compressive strength of the obtained multi-solid waste ultra-high performance concrete in Examples 1 to 4, which used a large amount of at least one of recycled micropowder and steel slag powder, and at least one of recycled aggregate and iron tailings sand, was ≥120 MPa, which met the requirements of ultra-high performance concrete. In particular, in Example 7, 30 parts of recycled micropowder and steel slag powder, and 60 parts of recycled aggregate and iron tailings sand were used relative to the sum of 46 parts of silica fume, fly ash and steel fiber, and the proportion of solid waste materials as coarse aggregate was relatively high, and the 28d compressive strength was 135.4 MPa, which met the requirements of ultra-high performance concrete, saved costs, and had significant economic and environmental benefits.
[0060] Compared with Comparative Example 1, in Comparative Examples 2 and 3 in which quartz sand is completely replaced by at least one of recycled aggregate and iron tailings sand, the sum of quartz sand: recycled aggregate and iron tailings sand is 0, and the 7d compressive strength of the obtained multi-solid waste ultra-high performance concrete is less than 100. In addition, the 28d compressive strength of Comparative Example 3 is less than 120 MPa.
[0061] It can be seen that the 28-day compressive strength of multi-solid waste ultra-high performance concrete containing at least one of recycled micropowder and steel slag powder, and at least one of recycled fine aggregate and iron tailings sand, with a mass ratio of cement: the sum of recycled micropowder and steel slag powder being 6:1-4:3, and quartz sand: the sum of recycled fine aggregate and iron tailings sand being 7:4-3:8, is ≥120 MPa, which meets the requirements of ultra-high performance concrete, saves costs, and has good economic and environmental benefits.
[0062] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A multi-solid waste ultra-high performance concrete, characterized in that: The invention comprises cement, silica fume, fly ash, steel fiber, quartz sand, water reducing agent, water, at least one of recycled micro powder and steel slag powder, and at least one of recycled fine aggregate and iron tailings sand, wherein, by mass ratio, the sum of cement: recycled micro powder and steel slag powder is 6:1-4:3, and the sum of quartz sand: recycled fine aggregate and iron tailings sand is 7:4-3:
8.
2. The multi-solid waste ultra-high performance concrete according to claim 1, characterized in that: The total amount of cement, recycled micro powder and steel slag powder is 70 parts relative to the total amount of silica fume, fly ash and steel fiber, which is 46 parts.
3. The multi-solid waste ultra-high performance concrete according to claim 1, characterized in that: The total amount of the quartz sand, recycled fine aggregate and iron tailings sand is 110 parts relative to the total amount of silica fume, fly ash and steel fiber, which is 46 parts.
4. The multi-solid waste ultra-high performance concrete according to claim 1, characterized in that: The regenerated micro powder is treated by mechanical activation, and the particle size reaches 8-20 μm.
5. The multi-solid waste ultra-high performance concrete according to claim 1, characterized in that: The steel slag powder is obtained by activating the steel slag powder under the conditions of a liquid-to-solid ratio of 0.2 and a carbon dioxide concentration of 20%.
6. The multi-solid waste ultra-high performance concrete according to claim 1, characterized in that: The quartz sand has a mesh size of 4 to 70.
7. The multi-solid waste ultra-high performance concrete according to claim 6, characterized in that: The mixing mass ratio of each particle size in the quartz sand is 4-10 mesh: 10-26 mesh: 26-40 mesh: 40-70 mesh = 252:245:116:
95.
8. The multi-solid waste ultra-high performance concrete according to claim 1, characterized in that: The water reducing agent has a water reducing rate of >30%.
9. A method for preparing multi-solid waste ultra-high performance concrete according to any one of claims 1 to 8, characterized in that: The steps include: (1) adding cement, silica fume, fly ash, and at least one of recycled micro powder and steel slag powder into a mixer and stirring to obtain a powder mixture; (2) adding water and a water reducing agent to the powder mixture obtained in step (1) while stirring, stirring for 1 to 2 minutes, then adding quartz sand and at least one of recycled fine aggregate and iron tailings sand, stirring for 1 to 3 minutes, and then adding steel fiber, stirring for 3 to 8 minutes, to obtain a high-solid waste ultra-high performance concrete.
10. Use of the multi-solid waste ultra-high performance concrete according to any one of claims 1 to 8 in building materials.
Citation Information
Patent Citations
Ultrahigh-performance concrete doped with steel residues and preparation method of ultrahigh-performance concrete
CN109592946A
Steel slag auxiliary cementing material and preparation method and application thereof
CN113072311A
Graphene oxide reinforced recycled aggregate ultra-high performance concrete and preparation method thereof
CN116217162A
Ultrahigh-performance iron tailing sand concrete and preparation method thereof
CN117923859A